2006
DOI: 10.1038/sj.ijo.0803333
|View full text |Cite
|
Sign up to set email alerts
|

Co-twin control designs for testing behavioral economic theories of child nutrition: methodological note

Abstract: Objective: To illustrate the use and potential efficiency of the co-twin control design for testing behavioral economic theories of child nutrition. Design: Co-twin control design, in which participating twins ate an ad libitum lunch on two laboratory visits. At visit 1, child food choices were not reinforced. On visit 2, twins were randomized to conditions such that one twin was reinforced for each fruit and vegetable serving consumed during lunch ('contingent') while his co-twin was reinforced irrespective o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 20 publications
(21 reference statements)
0
8
0
Order By: Relevance
“…This pattern is consistent with a substitution phenomenon, 40 such that increased fruit intake may have displaced juice intake. That fruits and vegetables can displace intake of energy-dense foods has been shown previously in children, 4,41 although it has not been demonstrated that increasing healthy foods can displace fruit juice intake per se. If true, such findings would support American Academy of Pediatrics' recommendations that whole fruits be used as an alternative for juice intake.…”
Section: Discussionmentioning
confidence: 89%
“…This pattern is consistent with a substitution phenomenon, 40 such that increased fruit intake may have displaced juice intake. That fruits and vegetables can displace intake of energy-dense foods has been shown previously in children, 4,41 although it has not been demonstrated that increasing healthy foods can displace fruit juice intake per se. If true, such findings would support American Academy of Pediatrics' recommendations that whole fruits be used as an alternative for juice intake.…”
Section: Discussionmentioning
confidence: 89%
“…We used the cotwin control design to test the effects of reinforcing fruit and vegetable intake on children's food selections and energy intake in the laboratory. 46 In sum, the cotwin control design may offer an elegant strategy for testing gene-by-environment interactions vis-à-vis child eating behavior. It has not been used to date for these purposes, although it has been used to address some issues pertinent to adult obesity.…”
Section: Cotwin Control Designsmentioning
confidence: 99%
“…Identifying factors that are related to obesity and are shared or common to parents and children may provide insight into the etiology of obesity, as well as factors that could be modified to simultaneously influence both parent and child weight in family-based behavioral obesity treatment programs. Research on behavioral genetics of behavioral economic variables is limited (Faith, Rose, Matz, Pietrobelli, & Epstein, 2006), and to our knowledge there have been no studies to assess parent-child relationships in relative reinforcing value of food or impulsivity. This experiment was designed to examine the relationship between parent and children responding in the context of choice experiments using relative reinforcing value and impulsivity paradigms.…”
mentioning
confidence: 99%